A Stage-structure Leslie-Gower Model with Linear Harvesting and Disease in Predator - Beay, Lazarus Kalvein; Leleury, Zeth Arthur; Rijoly, Monalisa E.; Lesnussa, Yopi Andry; Wattimena, Abraham Zacaria; Rahakbauw, Dorteus Lodewyik (Jambura Journal of Biomathematics (JJBM), 2023)
The growth dynamics of various species are affected by various aspects. Harvesting interventions and the spread of disease in species are two important aspects that affect population dynamics and it can be studied. In this work, we consider a stage-structure Leslie–Gower model with linear harvesting on the both prey and predator. Additionally, we also consider the infection aspect in the predator population. The population is divided into four subpopulations: immature prey, mature prey, susceptible predator, and infected predator. We analyze the existences and stabilities of feasible equilibrium points. Our results shown that the harvesting in prey and the disease in predator impacts the behavioral of system. The situation in the system is more complex due to disease in the predator population. Some numerical simulations are given to confirm our results.